Type I Hypersensitivity in Ferrets Following Exposure to SARS-CoV-2 Inoculum: Lessons Learned. (23rd June 2021) - Layton, Daniel; Burkett, Kathie; Marsh, Glenn A; Singanallur, Nagendrakumar B; Barr, Jennifer; Layton, Rachel; Riddell, Sarah-Jane; Brown, Sheree; Trinidad, Lee; Au, Gough G; McAuley, Alexander J; Lowther, Suzanne; et al.
Abstract: This case report discusses Type I hypersensitivity in ferrets following exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) inoculum, observed during a study investigating the efficacy of candidate COVID-19 vaccines. Following a comprehensive internal root-cause investigation, it was hypothesized that prior prime-boost immunization of ferrets with a commercial canine C3 vaccine to protect against the canine distemper virus had resulted in primary immune response to fetal bovine serum (FBS) in the C3 preparation. Upon intranasal exposure to SARS-CoV-2 virus cultured in medium containing FBS, an allergic airway response occurred in 6 out of 56 of the ferrets. The 6 impacted ferrets were randomly dispersed across study groups, including different COVID-19 vaccine candidates, routes of vaccine candidate administration, and controls (placebo). The root-cause investigation and subsequent analysis determined that the allergic reaction was unrelated to the COVID-19 vaccine candidates under evaluation. Histological assessment suggested that the allergic response was characterized by eosinophilic airway disease; increased serum immunoglobulin levels reactive to FBS further suggested this response was caused by immune priming to FBS present in the C3 vaccine. This was further supported by in vivo studies demonstrating ferrets administered diluted FBS also presented clinical signs consistent with a hyperallergic response, while clinical signs were absent in ferrets that received a serum-free SARS-CoV-2 inoculum. It is therefore recommended that vaccine studies in higher order animals should consider the impact of welfare vaccination and use serum-free inoculum whenever possible.